The Impact of Classroom Management on Elementary Students' Learning Quality - Rahayu, Puji; Haryati, Titik; Abdullah, Ghufron (Research, Training and Philanthropy Institution Natural Aceh, 2025)
Classroom management plays a vital role in shaping the quality of learning, particularly in elementary education, where foundational skills are developed. This study aimed to examine the influence of classroom management on the learning quality of elementary school students in Boja District, Kendal Regency. A quantitative research method with a correlational design was employed, involving 200 elementary teachers selected through proportionate stratified random sampling. Data were collected using validated Likert-scale questionnaires that measured classroom management across four dimensions and learning quality across four indicators. The findings revealed a strong positive correlation between classroom management and learning quality (r = 0.779, p < 0.01). Regression analysis revealed that classroom management has a significant predictive value for learning quality (B = 0.282), accounting for 60.6% of its variance. Among all components, time management was found to be the most influential aspect, while social interaction management showed the lowest effectiveness. These results underscore the importance of equipping teachers with both technical and interpersonal skills in classroom management.